PELAKSANAAN MANAJEMEN KOPERASI PADA KUD TANI MAKMUR DI JL. PETAPAHAN KEC. TAPUNG - Budi Sulistyo Hari Andini; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to develop core competencies and business concept cooperative accordance cooperatives business realities of Indonesian society folk-based economy. The study was conducted using a qualitative methodology, namely Beyond Structuralism. Beyond Structuralism synergize structuralist anthropology synchronous (contextual) and postrukturalis diachronic (the past). Methodology run with his methods Constructivist Structuralism Pierre Bourdieu to determine empirically (habitus, capital, field and practice) the cooperative business activity in Indonesia. The first phase, through the synergy of anthropology anthropological teoritisasi synchronous (cooperative business realities contextual) and anthropology diachronic (cooperative business realities initial phase). The second phase, to synergize both to find a common thread business cooperative concept of self-reliance in the field Teoritisasi empirically necessary to formulate the concept of the independence of the Cooperative.As a result, the concept of independence, the core competencies of family and productive synergy-retail-intermediation is the substance of cooperative development in accordance unique reality of Indonesian society. Although this is mostly reduced development time and subordination policy interventions great effort. Necessary policy, regulation, supporting the movement and strategic positioning with respect to regrow the concept of independence, the core competencies of family and productive synergy-retail-intermediation comprehensive.Keywords: Cooperative Management, Satisfaction Management, Cooperative